STUDI FILOSOFIS TERHADAP KONSEP ZUHUD DAN TAZKIYAH AN-NAFS DALAM KEHIDUPAN KONTEMPORER - Harahap, Nurhanipah (Academic Journal of Islamic Principles and Philosophy, 2025)
This study aims to explore the transcendental ethical dimension in the Sufi tradition through a philosophical examination of two key concepts: zuhud (asceticism, spirituality) and tazkiyah al-nafs (purification of the soul). This research is motivated by the phenomenon of contemporary life characterized by materialism, consumerism, and digital disruption that often erode human spiritual values. Instant lifestyles, an orientation towards instant gratification, and the increasing moral crisis indicate an urgent need to reintroduce transcendental values as a counterbalance. In this context, the concepts of zuhud and tazkiyah an-nafs in the treasury of Islamic Sufism are considered relevant for philosophical study. This article uses an Islamic philosophical approach and hermeneutic analysis. This research highlights the relevance of Sufi spiritual values ​​in addressing the ethical and spiritual crises that plague contemporary life. The concept of asceticism in Sufism is not merely understood as a rejection of the world, but also as a form of inner discipline that balances human relations with God and the world. Meanwhile, tazkiyah an-nafs serves as a foundation for ethical transformation, emphasizing self-honesty, controlling desires, and purifying life's orientation. In a modern context characterized by hedonism, consumerism, and existential alienation, these values ​​offer an alternative paradigm for building a holistic self-awareness and a life ethic oriented toward spiritual depth. This study concludes that transcendental ethics in Sufism can function as both cultural critique and a moral foundation for facing the challenges of humanity in the present era.